2021
DOI: 10.1002/tesq.3079
|View full text |Cite
|
Sign up to set email alerts
|

Linguistically Responsive Instruction for Latinx Teacher Candidates: Surfacing Language Ideological Dilemmas

Abstract: This qualitative study explored Linguistically Responsive Instruction (LRI) for linguistically diverse Latinx preservice Teacher Candidates (TCs) at a tertiary institution in the southwest region of the United States. To provide an example of preparing TCs to engage in LRI by helping them reflect upon ideological orientations, we operationalized LRI as a series of three reflective tasks-language portraits, ideology trees, and utterance analysis-designed to pose linguistic ideological dilemmas (LIDs) for partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…While it is unclear what these TCs understand by “fluency,” the reflections indicate that their understandings of language and speaking a language point to the ways that native speakerism (Aneja, 2016), standard language (Ek et al., 2013), and bilingualism‐as‐double‐monolingualism (Núñez & Espinoza, 2017) ideologies prevent them from claiming their bilingualism despite their reported functional ability in the language (see Figure 10). This was often the case of Latinx TCs who would position themselves as English monolinguals and later in the same document would confess that they understand Spanish (receptive skills), framing speaking a language (with particular accents) as the one determinant for proficiency and ability to claim the language (Lindahl et al., 2021). Still other participants who do claim their bilingualism, often described their language practices associated with Spanish as “Tex Mexy,” “street Spanish,” and as in need of improvement (Ek et al., 2013; Leeman, 2012; see Figure 11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is unclear what these TCs understand by “fluency,” the reflections indicate that their understandings of language and speaking a language point to the ways that native speakerism (Aneja, 2016), standard language (Ek et al., 2013), and bilingualism‐as‐double‐monolingualism (Núñez & Espinoza, 2017) ideologies prevent them from claiming their bilingualism despite their reported functional ability in the language (see Figure 10). This was often the case of Latinx TCs who would position themselves as English monolinguals and later in the same document would confess that they understand Spanish (receptive skills), framing speaking a language (with particular accents) as the one determinant for proficiency and ability to claim the language (Lindahl et al., 2021). Still other participants who do claim their bilingualism, often described their language practices associated with Spanish as “Tex Mexy,” “street Spanish,” and as in need of improvement (Ek et al., 2013; Leeman, 2012; see Figure 11).…”
Section: Resultsmentioning
confidence: 99%
“…One of the central purposes of these classes was to guide TCs to explore the sociopolitical dimension of language use and learning and to develop awareness of the pervasiveness of language ideologies. To accomplish this, we assigned TCs to complete a series of tasks—namely, language portraits, language awareness discussions, and language ideology trees (see Lindahl et al, 2021)—that enabled them to explore the ways they employ their linguistic repertoires as members of different communities and the ways language ideologies shape perceptions of their language practices. For this study, we selected participants who (a) self‐identified as Latinx broadly construed, and (b) made direct mention of language and ethnicity in their coursework.…”
Section: Methodsmentioning
confidence: 99%
“…Even when teachers understand the theory behind a critical language ideology, teacher-students often have difficulty moving from that abstract understanding to concrete practices (Lindahl et al, 2021). Nuñez and Espinoza (2019) found mentor teachers play a key role in uncovering and developing bilingual STs' supportive language ideologies, which also allowed STs to see how teachers have agency to challenge normative language practices and develop more inclusive practices.…”
Section: Education Research and Language Practicesmentioning
confidence: 99%
“…Nuñez and Espinoza (2019) found mentor teachers play a key role in uncovering and developing bilingual STs' supportive language ideologies, which also allowed STs to see how teachers have agency to challenge normative language practices and develop more inclusive practices. Another promising practice in developing critical language ideologies is incorporating local knowledge into the classroom (Espinoza et al, 2021;Lindahl et al, 2021;Seltzer, 2022). Intentionally building school-to-community relationships offers teachers a flexible approach to humanising language pedagogy in future classes.…”
Section: Education Research and Language Practicesmentioning
confidence: 99%
“…This is because being a linguistically responsive teacher involves not only the ability to utilize pedagogical skills to scaffold learning for CLD learners, but also a linguistically responsive orientation that includes an understanding of the sociolinguistic realities of CLD students and communities, an advocacy stance, valuing multilingualism, critical language awareness, and ideological clarity (Bartolomé, 2004; Brisk, 2013; De Costa, 2014; García, 2017; Lucas & Villegas, 2010). However, there is still widespread belief that working with CLD students is just good teaching (Coady, Harper, & de Jong, 2011; Li & Jee, 2021) without paying attention to ideological and sociopolitical aspects of teaching CLD students (Li, 2018; Lindahl, Fallas‐Escober, & Henderson, 2021). Even at university‐level teacher preparation programs, general teacher educators may lack logistical resources, expertise, or willingness to advocate for cultural and linguistic diversity (de Jong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%